2016
DOI: 10.1021/jacs.6b01966
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Synergism of Transferrin and Citrate in the Regulation of Ti(IV) Speciation, Transport, and Toxicity

Abstract: Human serum transferrin (sTf) is a protein that mediates the transport of iron from blood to cells. Assisted by the synergistic anion carbonate sTf transports Fe(III) by binding the metal ion in a closed conformation. Previous studies suggest sTf’s role as a potential transporter of other metals like titanium. Ti is a widely used metal in colorants, foods, and implants. A substantial amount of Ti is leached into blood from these implants. However, the fate of the leached Ti and its transport into the cells is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(128 citation statements)
references
References 52 publications
6
122
0
Order By: Relevance
“…Viability studies performed by our own lab have shown that even at 100 μM, this form of Ti(IV) shows no cytotoxicity. 33 Using these concentrations as a benchmark above which soluble Ti(IV) in serum would exhibit cytotoxicity, the amount of Ti(IV) released into the body even by implant sources should not pose a cytotoxic threat.…”
Section: Ti(iv) In the Bodymentioning
confidence: 99%
See 4 more Smart Citations
“…Viability studies performed by our own lab have shown that even at 100 μM, this form of Ti(IV) shows no cytotoxicity. 33 Using these concentrations as a benchmark above which soluble Ti(IV) in serum would exhibit cytotoxicity, the amount of Ti(IV) released into the body even by implant sources should not pose a cytotoxic threat.…”
Section: Ti(iv) In the Bodymentioning
confidence: 99%
“…A recent x-ray crystal structure we obtained of Ti(IV)-bound sTf, the first ever Ti(IV) protein structure, demonstrated sTf binding of Ti(IV) in a manner that is quite distinct from that of Fe(III). 33 The Ti(IV) is coordinated to only the two tyrosine residues in the metal binding site. The remainder of the coordination sites are fulfilled by carbonate and, in a surprise, citrate (Fig.…”
Section: Ti(iv) In the Bodymentioning
confidence: 99%
See 3 more Smart Citations